Awareness of the Importance of Children's Education in the Small Island Fisherman Community (Case Study of Liukang Loe Island) - Nismawati Nismawati; Shermina Oruh; Syamsu A. Kamaruddin; Andi Agustang; Mona Adria Wirda (JURNAL GEOGRAFI, 2023)
Residents of small island villages are typically classified as low-educated. This study used Liukang Loe Island as a case study to learn the truth about children's education in small island settlements. This study aims to determine how the fishing community understands the importance of education and how to increase public awareness about children's education on Liukang Loe Island. This study, which uses a descriptive qualitative technique with research informants, focuses on the "Harapan" fishing group community on Liukang Loe Island. Information was gathered through observation, interviews, and documentation. The type of analysis that was carried out by qualitative through taxonomic analysis, drawing conclusions using the Miles and Hubberman model, as well as directions to increase public awareness about the importance of education through AHP. The findings demonstrated that the Liukang Loe Island fishing community prioritized children's education, as seen by the community's, particularly families', efforts to ensure that children's education was completed. This is reinforced by the family's commitment to earning a living and covering all the children's educational demands. The fishing communities support their children's ability to advance to the highest level possible. Although there are only elementary and junior high schools on Liukang Loe Island, with limited facilities and infrastructure, children's enthusiasm and motivation to attend school are high. This does not deter the fishermen's children from continuing their high school and graduate education outside the island to obtain a better education. There are two options for raising awareness about education in fishing communities: community training and empowerment programs through NGOs, local governments, and educational institutions; and educational assistance programs in the form of notable scholarships for fishing communities in small islands.Keywords: Community Awareness, Fisherman, Education, Small Island